O papel dos bancos públicos federais na economia brasileira - Victor Leonardo de Araujo; Marcos Antonio Macedo Cintra (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper aims to present and analyze the functions performed by the Brazilian federal banks, in a Keynesian perspective, emphasizing its role: i) in promoting economic and regional development, by directing credit to specific sectors and regions, ii) the anti-cyclical action, especially after the financial crisis of 2008, iii) and the growth of banking of the Brazilian population of low income.
Keywords: G21; 330; Öffentliche Bank; Wirtschaftswachstum; Regionale Entwicklung; Antizyklisches Verhalten; Bankgeschäft; Niedrigeinkommen; Brasilien